P–696 The duration of estrogen treatment prior to frozen-blastocyst transfer does not impact live birth rate. (6th August 2021) - Reignier, A; Joly, J; Rosselot, M; Goronflot, T; Barrière, P; Fréour, T; Lefebvre, T
Abstract: Study question: Does the prolonged duration of oestrogen treatment prior to frozen-blastocyst transfer (FET) affect live birth rate? Summary answer: Variation in the duration of estrogen treatment prior to frozen-blastocyst transfer does not impact live birth rate. What is known already: With improvements in cryopreservation techniques and fertility preservation, single embryo transfer policy and the increase in freeze-all cycles, frozen blastocyst transfer (FET) has strongly risen over the last years. Artificial endometrial preparation (AEP) is often used prior to FET. The endometrium is prepared by a sequentially treatment of estrogen and progesterone in order to synchronize endometrium and the embryo development. Whether the duration of progesterone administration before FET is well established, the optimal estrogen treatment duration remains controversial. Study design, size, duration: All consecutive frozen thawed autologous blastocyst transfer cycles conducted between January 1, 2012 and July 1, 2019 in our University IVF center were included in this retrospective cohort study. We included 2235 single blastocyst FET cycles prepared with hormonal replacement therapy using oral E2 and vaginal progesterone administration in 1376 patients aged from 18 to 43 years. Participants/materials, setting, methods: Patient's characteristics, stimulation characteristics, FET cycles characteristics and cycles outcomes were anonymously recorded and analyzed. Univariate and multivariate analysis were performed. At first, each FET cycle was analyzed individually and secondly taking into account that some of the patients had undergone several FET, the model considered the number of implanting attempts for each woman. Main results and the role of chance: We found no significant difference in the mean duration of estradiol administration before frozen embryo transfer between the group live birth versus non-live birth (27.0 ± 5.4 days versus 26.6 ± 5.0 days ; p =0.11). Endometrial thickness was not significantly different between the 2 groups (8.3 ± 1.7 mm versus 8, 2 ± 1, 7 mm ; p = 0.21). When the duration of estradiol exposure was analyzed in weeks, we observed no difference for the £ 21 days group (OR = 0.97 ; IC 0.64–1.47 ; p = 0.88), 29–35 days group (OR = 0.89 ; IC 0.68–1.16 ; p = 0.37) and > 35 days group (OR = 0.75 ; IC 0.50–1.15 ; p = 0.10) compared to the reference group (22–28 days). After multivariate analysis, the duration of estradiol treatment before frozen embryo transfer did not affect live birth. Limitations, reasons for caution: The relatively limited numbers of cycles with more than 35 days or less than 21 days as well as the retrospective design of the study are significant limitations. Wider implications of the findings: Variation in the duration of estradiol supplementation before progesterone initiation does not impact FET outcomes. We therefore can be reassuring with our patients when E2 treatments need to be extended, allowing flexibility in scheduling the day of transfer. Trial registration number: Not applicable